English Language Teachers' Professional Development and Identities - Alberto Mora; Paulina Trejo; Ruth Roux (Universidad Nacional de Colombia, 2014)
This article analyzes the professional development of two English language teachers in a Mexican language center. In particular, it explores the interplay between professional development, identity and agency, and the part played by English language teaching certificates in all of these. Drawing on a case study methodology, which included the use of a series of three interviews and other qualitative data collection methods, the article demonstrates the intimate and intricate connection between teachers' identities and their professional development. Education implications for policy makers and practitioners are discussed.